Does financial depth impact economic growth in North Cyprus? - Turgut Türsoy; Faisal Faisal (Financial Innovation, 2018)
This study purpose is to connect the proxy of financial development which is total banking sector's deposits with the economic growth in North Cyprus. The reason for using the total deposit differently with the existing literature is because North Cyprus is bank-based financial system. Therefore, this study provides an analysis of the connection between finance-growth nexus in North Cyprus from 1978 through 2015, using the autoregressive distributed lag (ARDL) model and combined cointegration to evaluate and verify the relationship. In addition, this research added the inflation rate to the model specification to investigate the inflation-growth interaction. The results revealed that both methods of cointegration provided robust evidence for a long-run relationship between financial debt and growth. The ARDL long-run and short-run coefficients showed the positive impact of depth and the negative impact of inflation on economic growth, thereby confirming the strength of the finance-growth and inflation-growth connections. Moreover, financial depth had a larger coefficient than the inflation rate. Finally, the VECM Granger causality test provided evidence for unidirectional causality from the total deposits and inflation rate to economic growth in North Cyprus. These results are significant for the policymakers of North Cyprus because the findings show that economic growth can be improved by enhancing the deposit rates in the financial system.
Keywords: G21; C22; E40; 650; Financial depth; Inflation rate; Economic growth; ARDL; Granger causality